Women, class and society in early Christianity models from Luke - Acts - Arlandson, James Malcolm, 1956- (Peabody, MA Hendrickson, 1997)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. Luke -- criticism, interpretation, etc; Bible. N.T. Acts -- criticism, interpretation, etc; Women in the Bible; Women in Christianity -- history -- early Church ca.30 - 600.; Sociology, Biblical; Rome -- social life and customs